Kajian Kelembagaan Pengelolaan dan Sistem Terminal Bandar Raya Payung Sekaki Kota Pekanbaru - Hanafi, Ira Meutia (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The study examines the performance Dinas Perhubungan Komunikasi dan Informatika (Dishubkominfo) Kota Pekanbaru in the operation of Terminal Bandar Raya Payung Sekaki (BRPS) Kota Pekanbaru as a Type A terminal. The institutional sistem of Purabaya Terminal in Surabaya acted as a reference for best practice. The analysis included terminal institutional sistem analysis, terminal operation analysis, and terminal system analysis, followed by concluding the factors behind the poor performance of Terminal BRPS. Analysis showed that low human resources quality has lead to poor performance of Dishubkomunfo in operating the terminal. It has affected the policy planning and implementation, officer commitment and consistency, and the monitoring and enforcement whenever violations occur. Poor connectivity to the public transport system and low accessibility were identified to cause the poor performance of the terminal.